Correlation of serum hepatitis B core-related antigen with hepatitis B virus total intrahepatic DNA and covalently closed circular-DNA viral load in HIV–hepatitis B coinfection. (1st November 2020) - Dezanet, Lorenza N.C.; Maylin, Sarah; Gabassi, Audrey; Rougier, Hayette; Miailhes, Patrick; Lascoux-Combe, Caroline; Chas, Julie; Girard, Pierre-Marie; Delaugerre, Constance; Zoulim, Fabien; Lacombe, Karine; Boyd, Anders
Abstract : Objective: To assess whether quantified hepatitis B core-related antigen (qHBcrAg) is a surrogate marker of intrahepatic replication in HIV and hepatitis B virus (HBV) coinfection. Design: Cross-sectional study of 31 HIV–HBV-infected patients (total liver biopsies, n  = 38) from a well defined cohort. Methods: Spearman's rank correlation coefficients were calculated between qHBcrAg and intrahepatic markers of HBV replication [total intrahepatic-DNA, covalently closed circular (ccc) DNA, cccDNA : total intrahepatic-DNA ratio]. Results: At biopsy, 22 (71.0%) patients were hepatitis B 'e' antigen (HBeAg)-positive, 22 (71.0%) had detectable plasma HBV-DNA, and 17 (54.8%) were treated with tenofovir. Median levels (interquartile range) of intrahepatic markers were as follows: HBV cccDNA ( n  = 34), 0.26 copies/cell (0.4–2.89); total intrahepatic-DNA ( n  = 38), 2.38 copies/cell (0.58–207.9), and cccDNA : total intrahepatic-DNA ratio ( n  = 34), 0.05 (interquartile range = 0.01–0.12). There was a significantly strong correlation between qHBcrAg and cccDNA in all patients (Rho = 0.65, P  < 0.001), while a moderate correlation was observed between qHBcrAg and total intrahepatic-DNA (Rho = 0.57, P  < 0.001) or cccDNA : total intrahepatic-DNA ratio (Rho = −0.45, P  = 0.01). Similar findings were observed for HBeAg-positive patients and those with detectable HBV-DNA, with the exception of qHBcrAg and cccDNA or cccDNA : total intrahepatic-DNA ratio. In contrast, no significant correlation between qHBcrAg and any intrahepatic marker was observed in HBeAg-negative patients or those with undetectable HBV-DNA. No significant difference was observed in median qHBcrAg levels across liver fibrosis stages ( P  = 0.5). Conclusion: qHBcrAg is a potential surrogate marker of cccDNA in HIV–HBV coinfected patients, yet might be less useful with undetectable serum HBV-DNA or HBeAg-negative status. Whether qHBcrAg provides further clinical utility compared with other serological markers remains debatable. Abstract : Supplemental Digital Content is available in the text